Endovascular Treatment of Mycotic Aortic and Iliac Aneurysms in a Tertiary Center: A 15-Year Experience - Iakovos Theodoulou; Matthew Matson; Ounali Jaffer; Amr Elsaadany; Deborah Low; Ian Renfrew; Mohammed Rashid Akhtar (The Arab Journal of Interventional Radiology)
Objective This retrospective case series reports the 15-year experience of the endovascular management of mycotic aortic and iliac aneurysms (MAAs) at a tertiary referral center in the United Kingdom.